2022
DOI: 10.1007/s00894-022-05323-4
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth, crystal structure determination, and computational studies of a new mixed (NH4)2Mn1–xZnx(SO4)2(H2O)6 Tutton salt

Abstract: Tutton salts have been extensively explored in recent decades due to their attractive physical and chemical properties, which make them potential candidates for thermochemical heat storage systems and optical technologies. In this paper, a series of new mixed Tutton salts with the chemical formula (NH4)2Mn1–xZnx(SO4)2(H2O)6 is reported. Crystals are successfully grown by the solvent slow evaporation method and characterized by powder X-ray diffraction (PXRD) with Rietveld refinement. In particular, the crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Secondly, electronegativity χ-metals with greater electronegativity (χ(Ni) = 1.91 and (χ(Cu) = 1.90) exhibit greater occupations of divalent sites due to the greater tendencies to attract electrons when compared to Mn (χ(Mn) = 1.55). Thirdly, intermolecular interactions-the Mn(II) hexa-aqua complexes are highly unstable; however, in some Tutton salts, this metal presents stability due to hydrogen bonds, as is true in the case of crystals of (NH 4 ) 2 Mn(SO 4 ) 2 (H 2 O) 6 [44] and (NH 4 ) 2 Mn 0.5 Zn 0.5 (SO 4 ) 2 (H 2 O) 6 [29]. On the other hand, weak interactions that destabilize [Mn(H 2 O) 6 ] 2+ complexes, such as ion-dipole and dispersion forces, are also observed in the atomic packing of potassium Tutton salts.…”
Section: Structure Solving and Lattice Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, electronegativity χ-metals with greater electronegativity (χ(Ni) = 1.91 and (χ(Cu) = 1.90) exhibit greater occupations of divalent sites due to the greater tendencies to attract electrons when compared to Mn (χ(Mn) = 1.55). Thirdly, intermolecular interactions-the Mn(II) hexa-aqua complexes are highly unstable; however, in some Tutton salts, this metal presents stability due to hydrogen bonds, as is true in the case of crystals of (NH 4 ) 2 Mn(SO 4 ) 2 (H 2 O) 6 [44] and (NH 4 ) 2 Mn 0.5 Zn 0.5 (SO 4 ) 2 (H 2 O) 6 [29]. On the other hand, weak interactions that destabilize [Mn(H 2 O) 6 ] 2+ complexes, such as ion-dipole and dispersion forces, are also observed in the atomic packing of potassium Tutton salts.…”
Section: Structure Solving and Lattice Parametersmentioning
confidence: 99%
“…Several mixed Tutton salts, such as K 2 Ni x Co 1−x (SO 4 ) 2 (H 2 O) 6 [28], (NH 4 ) 2 Ni x Co 1−x (SO 4 ) 2 (H 2 O) 6 [15], (NH 4 ) 2 Mn 1−x Zn x (SO 4 ) 2 (H 2 O) 6 [29], K 2 Zn x Mg 1−x (SO 4 ) 2 (H 2 O) 6 [30], and (NH 4 ) 2 Ni x Cu 1−x (SO 4 ) 2 (H 2 O) 6 [31], have been explored as materials for ultraviolet light filters and solar-blind devices. Recently, there has been great interest in thermochemical applications, where materials can store energy in the heat form by heating water [2,3,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Neto et al 19 concluded in a new and interesting study that these crystals can be applied in thermochemical systems for thermal energy storage and also evaluated the empty spaces present in the unit cells of their crystals through electronic density isosurfaces, showing that high percentage of empty spaces can cause a decrease in the energy of interactions affecting physicochemical parameters such as solubility, dissolution, and hardness of crystalline structures. On the other hand, these empty spaces can be filled by dopants in order to strengthen these intermolecular interactions in order to increase, for example, the thermal stability of the crystals.…”
Section: Introductionmentioning
confidence: 99%